The efficacy of fluticasone furoate administered in the morning or evening is comparable in patients with persistent asthma. (March 2016) - Kempsford, R.D.; Bal, J.; Baines, A.; Renaux, J.; Ravindranath, R.; Thomas, P.S.
Abstract: Background: The inhaled corticosteroid fluticasone furoate (FF) is efficacious as a once-daily treatment for the management of asthma. Asthma is associated with circadian changes, with worsening lung function at night. We compared the efficacy of once-daily FF in the morning or evening for the treatment of asthma. Methods: Adults with persistent bronchial asthma were enrolled into this randomised, repeat-dose, double-blind, double-dummy, placebo-controlled, three-way crossover study. After a 14-day run-in period, patients received either: FF 100 μg in the morning (AM); FF 100 μg in the evening (PM); or placebo, via the ELLIPTA ® dry powder inhaler. Patients received all three treatments (14 ± 2 day duration) separated by a 14- to 21-day washout period. The primary endpoint was 24-h weighted mean forced expiratory volume in 1 s (FEV1 ) measured at the end of each 14-day treatment. Results: A total of 28 patients aged between 19 and 67 years were randomised and 21 (75%) completed all three study arms. Once-daily administration of FF 100 μg resulted in an increased 24-hour weighted mean FEV1 ; differences between the adjusted means for AM and PM FF dosing versus placebo were 0.077 L (90% confidence interval [CI]: 0.001, 0.152) and 0.105 L (90% CI: 0.029, 0.180), respectively (adjusted mean difference: –0.028 L [90% CI: –0.102, 0.045]). AM or PM doses had comparable incidences of adverse events (AEs; 18/23 versus 18/24, respectively), no serious AEs occurred. Conclusion: AM and PM doses of once-daily FF 100 μg produced comparable improvements in lung function relative to placebo. Highlights: Timing of once-daily fluticasone furoate (FF) was studied for efficacy in asthma. Morning (AM) or evening (PM) FF100 μg, and placebo were compared. Forced expiratory volume in 1 s (FEV1) was measured on Day 14. AM and PM dosing were comparable for 24-h and pre-treatment FEV1. There was also no difference in adverse event incidence between AM and PM dosing.